Are They Important? Patients' Communication Barriers to Discussing Online Health Information During Consultations - Linn, Annemiek J.; van Weert, Julia C. M.; Bylund, Carma L. (Health communication, 2024)
A minority of the patients who search for online health information report discussing or having an intention to discuss this information with their healthcare provider. Not discussing online health information inhibits the provision of patient-centered care and limits the healthcare provider's possibility to tackle misinformation. Within the confines of the linguistic model of patient participation, we first provide an overview of barriers to discussing online health information during consultations. Second, we pinpoint which of these barriers indicate a need for improvement. Participants from the Netherlands (N = 300) completed a survey that measured the communication barriers (N = 15) as identified based on previous literature and interviews. Using the QUality Of Care Through the patient's Eyes (QUOTE) approach, we measured the extent to which a specific factor was a barrier ("importance") and assessed whether the barrier would withhold patients from discussing online health information ("performance"). Scores on importance and performance were multiplied to identify which barriers show the most significant room for improvement. Especially "preferring to discuss other matters" often occurred. Nine barriers showed a moderate need for improvement. We discuss the implications of these findings for healthcare providers in consultations. Future research should include observational data to analyze communication barriers to discussing online health information in consultations.